2010
DOI: 10.1007/s11033-010-0359-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study

Abstract: To examine the interaction between IL-1F7 gene and environmental factors in patients with ankylosing spondylities (AS). 150 AS Han Chinese patients (all human leukocyte antigen-B27 positive) were genotyped using a panel of single-nucleotide polymorphism markers within IL-1F7 gene (rs3811047) by ligase detection reactions. Polymerase chain reaction with sequence-specific primer was used to determine HLA-B27 subtypes. We analyzed the interaction between IF-1F7 gene and eight environmental factors in AS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
2
18
0
1
Order By: Relevance
“…Previous reports suggested that IL37 was involved in the development of various inflammatory conditions, including ankylosing spondylitis and rheumatoid arthritis. [23][24][25] However, all these studies were based on genotyping rs3811047:A4G, which result in c.124A4G (p.(Thr42Ala)) substitution and does not differentiate between major IL37 variants identified in this study. On the basis of our data, we recommend genotyping any one of the five non-synonymous SNPs, rs2708943:C4G, rs2723183: A4G, rs2723187:C4T, rs2708947:C4T or rs2723192:A4G, to differentiate between IL37 haplogroups 1 and 2, which differ at least at five non-synonymous sites and probably result in different susceptibility to human diseases.…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports suggested that IL37 was involved in the development of various inflammatory conditions, including ankylosing spondylitis and rheumatoid arthritis. [23][24][25] However, all these studies were based on genotyping rs3811047:A4G, which result in c.124A4G (p.(Thr42Ala)) substitution and does not differentiate between major IL37 variants identified in this study. On the basis of our data, we recommend genotyping any one of the five non-synonymous SNPs, rs2708943:C4G, rs2723183: A4G, rs2723187:C4T, rs2708947:C4T or rs2723192:A4G, to differentiate between IL37 haplogroups 1 and 2, which differ at least at five non-synonymous sites and probably result in different susceptibility to human diseases.…”
Section: Discussionmentioning
confidence: 86%
“…After further consideration, 3 abstracts were removed because they did not include the necessary information and 46 full-text articles were removed because they did not report AS (n=3), did not look at relationship between AS and diet (n=2), included children (n=1), had a very small sample of AS patients (n=4), contained case reports (n=3), did not report information on diet (n=1), was in the Chinese language (n=1), did not report diet (n=25), did not report information on AS (n=2), and were non-systematic reviews (n=3) and thesis (duplicate publication, n=1). There were a total of 16 studies included in the review, 10 of which were full-text papers, two were letters, two studies were summarized in review articles, and two were conference abstracts (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Search Resultsmentioning
confidence: 99%
“…Description of the included studies and participants Multiple studies were conducted in Sweden and United Kingdom, and individual studies in Norway, Belgium, France, Australia, New Zealand, China, Portugal, and Turkey (Table 1, Appendix 1) and were published between 1991 and 2014 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(37)(38)(39)(40). Seven of the included studies were case series; three were treatment outcome studies with all the participants receiving intervention, three were randomized clinical trials, one was a case-control study, and one study investigated the gene-environment interaction using a case-only design (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(37)(38)(39)(40).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations